Influence of Adversity Quotient on Academic Stress among 2022 PAI Students at UIN Raden Intan Lampung - Dwina, Indri; Syafe’i, Imam; Irawan, Rudy (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This study aims to examine the effect of Adversity Quotient (AQ) on academic stress among 2022 cohort students of the Islamic Education Study Program (PAI) during the completion of their final project at UIN Raden Intan Lampung. Academic stress is defined as physical, emotional, cognitive, and behavioral pressure resulting from academic demands, whereas AQ reflects students’ ability to face difficulties and endure stress. The study was conducted in the odd semester of 2025/2026 with a population of 388 students and a sample of 79 respondents selected using simple random sampling based on Slovin’s formula. The instrument was a 30-item Likert-scale questionnaire, which was validated and reliable (Cronbach’s Alpha: AQ = 0.965; academic stress = 0.975). Data were analyzed using simple linear regression after confirming normality and linearity assumptions. Results indicate that AQ has a significant negative effect on academic stress (t = –11.519; p = 0.000), with a strong relationship (R = 0.795) and 63.3% of stress variation explained by AQ. Students with higher AQ are better able to self-regulate, handle pressure, and employ adaptive coping strategies. The findings underscore the importance of enhancing AQ through mentoring, problem-solving training, and resilience-based counseling to reduce academic stress.